PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMEN PRIMER - Pajriah; Hanifah; Mike Mega Rahayu (The Asia Pacific Journal Of Management Studies, 2023)
This research aims to examine the effect of Return On Asset (ROA), Return On Equity (ROE) and Current Ratio (CR) on the stock prices in consumer non cyclicals company on the Indonesia Stock Exchange (IDX) for the period of 2017-2021. Used in this research is quantitative research. The data used is sourced from financial data on the Indonesia Stock Exchange trought the website www.idx.co.id. The population used in this study were consumer non cyclicals companies and has been selected based on predetermined criteria using a purposive sample the samples obtained were 35 companies. The data analysis method used the classical assumption test and multiple linier regression with partial test (t-test) and simultaneous test (F-test) the using SPSS V.26. The results of this study indicate that parttialy Return On Asset (ROA) has influence and significant effect on stock prices, Return On Equity (ROE) and Current Ratio (CR) has not effect significant on stock prices. Simultaneous calculation results Return On Asset (ROA), Return On Equity (ROE) and Current Ratio (CR) have an effect and significant on stock prices..